Vitamin D Deficiency in Relapsing Anti-NMDAR Encephalitis Presenting with Acute Cognitive Impairment: A Case Report - Audiza Luthffia; Cempaka Thursina Srie Setyaningrum; Amelia Nur Vidyanti; Desin Pambudi Sejahtera; Sekar Satiti (Magna Neurologica, 2025)
Background: Anti N-methyl-D-aspartate Receptor (NMDAR) encephalitis is an autoimmune disease characterized by neuropsychiatric symptoms caused by autoantibodies against NMDAR. It is a treatable disease, but approximately 12-25% of  patients experience relapse. Vitamin D has several immunomodulatory effects and its deficiency is associated with systemic and neurologic autoimmune disease. Case:A 21-year-old woman presented with acute cognitive impairment, followed by status epilepticus during hospitalization. Two years ago, she was diagnosed with anti-NMDAR encephalitis and completely recovered after immunotherapy. During relapse, magnetic resonance imaging (MRI) showed chronic lacunar infarct on the right basal ganglia, and electroencephalography (EEG) showed diffuse slowing, identical to findings from the first event. Laboratory testing during relapse indicated vitamin D deficiency, which was normal before relapse onset. Symptoms improved following intravenous methylprednisolone, plasma exchange, vitamin D supplementation, and symptomatic treatment. Discussion: Inadequate immunotherapy has been suggested as a major risk factor for relapse, while other determinants have not been well recognized. Vitamin D inhibits proliferation of B cells, an important immunomodulator in anti-NMDAR encephalitis. Previous study revealed vitamin D levels were reduced in anti-NMDAR encephalitis patients and it is also thought to influence response to therapy. On the other hand, vitamin D also influence neurotransmitter activities and synaptic formation involved in cognitive and memory functioning. Conclusion: Anti-NMDAR encephalitis is a treatable autoimmune disease but still has the possibility of relapse. Vitamin D deficiency may be related with relapse of anti-NMDAR encephalitis. Routine screening for vitamin D deficiency can be considered in relapsed patients or during maintenance therapy.